Perspectiva de los brasileños sobre la intención de adopción y la eficacia de las plataformas digitales para el aprendizaje en línea durante el COVID-19 - dos Santos Bortolocci Espejo, Márcia Maria (2022)
Objective: To identify the factors that influence the adoption of technological tools by business students during the pandemics. Method: Quantitative with the submission of an online quiz to students of a Brazilian university which was estimated by a Structured Equation Model. Results: The perceived usefulness and ease of use of a technological tool do not have a positive influence on the students' attitudes towards its use; at the same time, a positive relation was found between the interactivity and the cost-benefit ratio of the platforms and students' attitudes. Conclusion: It can be concluded that offering a digital teaching platform with resources that allow high interaction between students and instructors and does not involve high costs for students, can help to increase the willingness to use the platform.